The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4047/jap.2018.10.4.308
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nonthermal argon plasma on the shear bond strength between zirconia and different adhesives and luting composites after artificial aging

Abstract: PURPOSEPlasma activation of hydrophobic zirconia surfaces might be suitable to improve the bond strength of luting materials. The aim of this study was to analyze the influence of nonthermal argon-plasma on the shear bond strength (SBS) between zirconia and different combinations of 10-MDP adhesive systems and luting composites after artificial aging.MATERIALS AND METHODSTwo hundred forty Y-TZP specimens were ground automatically with 165 µm grit and water cooling. Half of the specimens received surface activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
(33 reference statements)
2
18
0
Order By: Relevance
“…Irrespective of the cement type, the SBS values of the NTP group were significantly lower in thermocycling than non-thermocycling. These results are consistent with previous reports of a significant decrease in SBS due to thermocycling after NTP treatment [23,25,38]. Therefore, the SBS after NTP treatment may be affected by thermal stress, the compositions of resin cement, and low resistance to hydrolysis of the van der Waals bond [39,40].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Irrespective of the cement type, the SBS values of the NTP group were significantly lower in thermocycling than non-thermocycling. These results are consistent with previous reports of a significant decrease in SBS due to thermocycling after NTP treatment [23,25,38]. Therefore, the SBS after NTP treatment may be affected by thermal stress, the compositions of resin cement, and low resistance to hydrolysis of the van der Waals bond [39,40].…”
Section: Discussionsupporting
confidence: 92%
“…Some articles also have mentioned that this mechanical surface treatment can improve the bond strength between zirconia and various types of cement [29,30]. In contrast, several studies have shown that the microporosity created by sandblasting can act as a cracking agent to worsen the long-term stability of zirconia-based restorations [4,7,22,25]. Additionally, He et al [31] have also been mentioned that the remaining Al 2 O 3 particles after sandblasting could degrade the adhesion, requiring the cleaning of the surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, NTP generation equipment is not only inexpensive but also low in maintenance costs [ 31 ]. This NTP processing has been introduced to dentistry and may be an effective tool for increasing the RS of the zirconia crown [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several articles have reported the effect of NTP on shear bond strength or microtensile bond strength between zirconia and resin cement [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. However, there is currently no study on the RS between NTP-treated zirconia crown and titanium implant abutment through resin cement.…”
Section: Introductionmentioning
confidence: 99%